2022
DOI: 10.1016/j.it.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

K63 ubiquitination in immune signaling

Abstract: Ubc13-catalyzed K63 ubiquitination is a major control point for immune signaling. Recent evidence has shown that the control of multiple immune functions, including chronic inflammation, pathogen responses, lymphocyte activation, and regulatory signaling, is altered by K63 ubiquitination. In this review, we detail the novel cellular sensors that are dependent on K63 ubiquitination for their function in the immune signaling network. Many pathogens, including severe acute respiratory syndrome coronavirus 2 (SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 127 publications
1
25
0
Order By: Relevance
“…Polyubiquitination through K48 of ubiquitin leads to proteasomal degradation, and K63-linked ubiquitin plays a role in signaling, endocytosis, or even regulating kinase activation ( Sadowski and Sarcevic, 2010 ). It was demonstrated that ubiquitination via K63 is important for the regulation of signal transduction by multiple receptors of both innate and adaptive immunity, including the TLRs, NLRs, TNFR, T- and B-cell antigen receptors and many other ( Madiraju et al, 2022 ).…”
Section: Components Contributing To Proteostasismentioning
confidence: 99%
“…Polyubiquitination through K48 of ubiquitin leads to proteasomal degradation, and K63-linked ubiquitin plays a role in signaling, endocytosis, or even regulating kinase activation ( Sadowski and Sarcevic, 2010 ). It was demonstrated that ubiquitination via K63 is important for the regulation of signal transduction by multiple receptors of both innate and adaptive immunity, including the TLRs, NLRs, TNFR, T- and B-cell antigen receptors and many other ( Madiraju et al, 2022 ).…”
Section: Components Contributing To Proteostasismentioning
confidence: 99%
“…So far, the most thoroughly characterized polyubiquitin processes are lysine 48 (K48)-and K63-linked ubiquitination. K48-linked chains prefer to target proteins for proteasomal degradation, while K63-linked chains act as a molecular glue for complex formation in various signaling pathways and also participate in protein degradation (Grice & Nathan, 2016; Hayden & Ghosh, 2008; Liu et al, 2018; Madiraju et al, 2022; Wang et al, 2022). We next examined which sites of polyubiquitin chains attached to ERα could be removed by MYSM1.…”
Section: Resultsmentioning
confidence: 99%
“…MYSM1 belongs to the JAMM family of deubiquitinase, so we hypothesized it may participate in maintenance of ERα stability through its deubiquitinase activity. Next, we turned to perform western blot to detect the effect of full length of MYSM1 to target proteins for proteasomal degradation, while K63-linked chains act as a molecular glue for complex formation in various signaling pathways and also participate in protein degradation (Grice & Nathan, 2016;Hayden & Ghosh, 2008;Liu et al, 2018;Madiraju et al, 2022;Wang et al, 2022). We next examined which sites of polyubiquitin chains attached to ERα could be removed by MYSM1.…”
Section: Mysm1 Stabilizes the Erα Protein With Its Deubiquitination A...mentioning
confidence: 99%
“…The table below shows representative compounds tested for Cbl-b inhibition and the biological data obtained from testing representative examples. …”
Section: Important Compound Classesmentioning
confidence: 99%